Lean Safety Model to reduce accidents in conventional subway mining haulage activities - Risco-Carbonel, Jorge (2023)
Safety in the mining industry is of vital importance, since it involves high-risk work, with activities in confined spaces, at heights, with suspended loads, among others. For this reason, it is necessary to use different methodologies to prevent and control the dangers present in mining works. Having this data and establishing that the dependent variable of accidents in haulage activities are substandard acts and conditions, we have proposed to implement the lean safety methodology, a Lean Management approach, which will allow us to reduce waste (accidents that reduce the value of the product), in this case in haulage activities. For the implementation of this methodology, we used 3 phases, which are Lean initiation, Lean Implementation, Lean Sustainability. The present results reveal the efficiency of this methodology to reduce downtime, accidents and increase prevention activities, such as training, audits and standards for the development of haulage in conventional subway mining.